Mindfulness Therapy on Adolescent’s Anxiety and Depression: A Systematic Review - Nanik Lestari; Efendi, Ferry; Qur'aniati, Nuzul; Yunara, Yulia (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Globally, there is an increase in mental health issues. The prevalence of mental health issues among 10 to 19-year-olds is estimated to be 1 in 7 (14%) globally, despite the fact that most of these conditions go undiagnosed and untreated. Mindfulness techniques have been employed consistently, and has suggested associated criteria for the treatment of depression. Objective: This systematic review was carried out to analyze relevant articles about the effectivity of mindfulness therapy to anxiety and depression on adolescent. Methods: The Preferred Reporting Items For Systematic Review And Meta-Analysis (PRISMA) and the Joanna Briggs Institute (JBI) checklist provided as a guidance. The data conducted in Science Direct, ProQuest, SAGE, and Pubmed databases. The articles were published in the last five years. Results: In the final review, twelve articles were include. The articles were heterogeneous, RCT designs was used the most. Some of them also use mindfulness therapy that have been combined. Significant impacts of mindfulness therapy on adolescents have been found, particularly in the areas of anxiety and depression. Conclusion: It is crucial to understanding how mindfulness works during childhood and adolescence, as well as what type, dose, and frequency of therapy are most recommended.